Unresectable stage III non-small cell lung cancer: is Tecemotide a new START for our patients? - Wauters, Els; Johan, Vansteenkiste (Journal of Thoracic Disease, 2014)
Approximately one third of all non-small cell lung cancer (NSCLC) patients present with unresectable locally advanced stage III disease. The treatment of these patients remains one of the major challenges of contemporary oncology. During the past three decades, gradual progress has been made in the curative-intent treatment. In the 80-ies, these patients were treated with radiotherapy as a single modality, resulting in a median overall survival (OS) of about 10 months. In a landmark trial in early 90ies, it became clear that adding cisplatinbased chemotherapy to radiotherapy improved median OS from approximately 10 to 14 months (1). Subsequent studies established that concurrent delivery of both modalities further improved median OS by an additional 4 months to 18 months, compared with sequential delivery, which corresponded to an absolute 4.5% gain in 5-year OS to 15.1% (2). Based on these results, the concurrent delivery of 60 Gy of chest radiation and two cycles of cisplatin-based doublet chemotherapy is our current standard of care for fit patients with unresectable stage III NSCLC (3).